2023
DOI: 10.3389/fped.2023.1152083
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of anemia among children aged from 6 to 59 months in Liberia: a multilevel analysis of the 2019/20 Liberia demographic and health survey data

Abstract: BackgroundAnemia is a serious worldwide public health issue that happens at any stage of life but primarily affects young kids and pregnant mothers. Although anemia has a significant impact on child health, its magnitude and associated factors in children aged 6–59 months have not been yet studied in Liberia. Therefore, the aim of this study was to identify the prevalence and determinants of anemia in children aged 6–59 months in Liberia.MethodsThe data was extracted from Liberia Demographic and Health Survey,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…A study by Kothari et al found mixed findings on the associations between the water source and anaemia in the analysis of 47 demographic and health surveys [ 76 ]. However, only some studies conducted in Zimbabwe [ 77 ] and Liberia [ 78 ] found a significant association between the use of unimproved sources of drinking water and anaemia in children. These conflicting findings may result from various infectious disease pathogens in various environments, dietary patterns, and other behavioural factors related to water handling and treatment that may influence the relationship between anaemia and the household water source.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Kothari et al found mixed findings on the associations between the water source and anaemia in the analysis of 47 demographic and health surveys [ 76 ]. However, only some studies conducted in Zimbabwe [ 77 ] and Liberia [ 78 ] found a significant association between the use of unimproved sources of drinking water and anaemia in children. These conflicting findings may result from various infectious disease pathogens in various environments, dietary patterns, and other behavioural factors related to water handling and treatment that may influence the relationship between anaemia and the household water source.…”
Section: Discussionmentioning
confidence: 99%
“…Defined broadly as a condition associated with lower-than-normal hemoglobin concentration, anemia impairs the circulation of oxygen in the blood, which in turn has detrimental effects on suboptimal child growth, impaired learning, and reduced work productivity and income earning during adulthood [1]. For children between 6 and 59 months (generally referred to as under-fives), the threshold Hb level for being nonanemic is 11.0 grams per deciliter.…”
Section: Introductionmentioning
confidence: 99%
“…For children between 6 and 59 months (generally referred to as under-fives), the threshold Hb level for being nonanemic is 11.0 grams per deciliter. Anemia diagnosis is classified as mild (Hb=10.0-10, moderate (Hb=7.0-9.9 g/dl), severe (Hb<7.0g/dl), and normal (Hb≥11.0 g/dl) Hb level concentration for children aged 6 to 59 months [1,2]. Approximately 50%of anemia cases are due to iron deficiency, though the proportion varies among population groups and in different areas, according to the prevailing local conditions [3].…”
Section: Introductionmentioning
confidence: 99%